Simulador didático de ondas viajantes para diferentes topologias de sistemas de potência - Cruz, Francisco Marks da (Brasil, 2017)
The model of education in the last decades has undergone considerable changes from a didactic point of view. With the advancement of technology, the speed of obtaining information increases and the use of tools that allow the dynamic visualization of content becomes a strong ally to the teaching-learning process. This work deals with the creation of an interactive tool to visualize the propagation of traveling waves in an electric power system, with the possibility of insertion of data by the user, in order to facilitate the consolidation of knowledge. The model was created from the GUIDE of Matlab R, which has a graphical interface with the possibility of inserting data into a single screen with action buttons, which when clicked performs actions like calculate and display the animated graphic. It is important to highlight that the creation of the program, besides facilitating the student's understanding, due to the animation, also allow a better familiarization with computer simulation software, and with the parameters used in the transient analysis in transmission lines
Didactic simulator for traveling waves for differens topologies of power systems
Keywords: Ondas viajantes; GUIDE do MATLAB R; Simulação computacional; Animação no MATLAB R; Traveling waves; MATLAB GUI; Computer simulation; Animation in MATLAB; ENGENHARIAS::ENGENHARIA ELETRICA